If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13x + -6) + -6(2x + 2) = -6 Reorder the terms: (-6 + 13x) + -6(2x + 2) = -6 Remove parenthesis around (-6 + 13x) -6 + 13x + -6(2x + 2) = -6 Reorder the terms: -6 + 13x + -6(2 + 2x) = -6 -6 + 13x + (2 * -6 + 2x * -6) = -6 -6 + 13x + (-12 + -12x) = -6 Reorder the terms: -6 + -12 + 13x + -12x = -6 Combine like terms: -6 + -12 = -18 -18 + 13x + -12x = -6 Combine like terms: 13x + -12x = 1x -18 + 1x = -6 Solving -18 + 1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 1x = -6 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = -6 + 18 1x = -6 + 18 Combine like terms: -6 + 18 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 400+300/20 | | 0.5x+6=x+5/3 | | 2/x-2=-4/x+4+18/(x-2)(x+4) | | 2u-54=-u+21 | | 8a=65-100n | | 400+(15x200)/200 | | (6h-7)/h | | (-7/12)-(-3/8)=0 | | 4x+32=4x+26 | | (17x-9)-8(2x+4)=-5 | | -7/12-(-3/8)=0 | | (10/11)x+(1/3)=(2/5)-(1/11)x+(2/5) | | y=2ZX+2ZY+2XY | | L=0.4L+6 | | -9h=u | | (2/3)x+(1/2)=(3/7)-(1/3)x+(3/7) | | (-2v/9)=-6 | | (-7/2y)=-21 | | [x+3]=7x-4 | | (-5/6v)=20 | | Y=4x-160 | | 5/3x+1/3x=131/3+8/3 | | ln(2x+14)-ln(x+2)=ln(x-5) | | 3(u-5)-9=-6(-2u+2)-u | | 1.89/12 | | 8(v+2)+3v+7=6v+7 | | -2(x-4)-20=-12 | | (5/4)^-3 | | 5-c-2=3+4x+5 | | 6y-3=-6x+3 | | (7/5)^-2 | | 5-x-2=3+4*4x+5 |